Overview of Forensic Toxicology, Yesterday, Today and in the Future - Chung, Heesun; Choe, Sanggil (Current Pharmaceutical Design, 2017)
Background: The scope of forensic toxicology has been tremendously expanded over the past 50 years. From two general sections forensic toxicology can be further classified into 8-9 sections. Methods: The most outstanding improvement in forensic toxicology is the changes brought by instrumental development. The field of forensic toxicology was revolutionized by the development of immunoassay and benchtop GC-MS in the 1980's and LC-MS-MS in 2000's. Detection of trace amounts of analytes has allowed the use of new specimens such as hair and oral fluids, along with blood and urine. Over a longer period of time, continuous efforts have been made to efficiently extract and separate drug and poison from biological fluids. International endeavors to develop high quality standards and guidelines for drugs and poisons in biological specimens and to promote them in order to increase reliability of laboratories are also part of the recent advancement of forensic toxicology. Interpretation of postmortem toxicology encompasses various factors including postmortem redistribution and stability. Results: Considering the recent trend, the interpretation of toxicological results should account for autopsy findings, crime scene information, and related medical history. The fields of forensic toxicology will continuously develop to improve analysis of target analytes from various specimens, quality assurance program, and results interpretation. In addition, the development of analytical techniques will also contribute further advancement of forensic toxicology. Conclusion: The societies of forensic toxicologists, such as TIAFT, will play an important role for the advancement of forensic toxicology by collaborating and sharing ideas between toxicologists from both developed and developing countries.
Keywords: quality assurance